The Lottery as a Democratic Institution - Stone, Peter (The Policy Institute, 2013)
Proponents of random selection in politics have identified at least eight potential contributions that the practice can make to the political process. These are: descriptive representation, prevention of corruption and/or domination, mitigation of elite-level conflict, control of political outliers, distributive justice, participation, rotation, and psychological benefits. We argue that random selection makes its strongest contribution when it selects citizens to function as impartial guardians of the political system. This means selecting citizens at random, not to make policy or enact laws, but to protect the integrity of the political process?by making and enforcing legislative ethics standards, for example. Random selection?s strongest contribution is to the prevention of corruption and/or domination; the fact that it enables descriptive representation, while undeniably true, is less important to politics.
PUBLISHED
Keywords: lottery; democracy; representation; corruption; random selection; sortition